Farming Of Red Chili And The Green Chili During The Plague Of Covid-19 - Nurhajijah Nurhajijah; Fitria Fitria; Ade Firmansyah Tanjung (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2021)
Covid-19 is a disease caused by the corona virus. In this situation, it makes new changes from all aspects of life, one of which is a change in the food supply chain. This change in situation greatly affected the red chili farmers. At the time of the pandemic, it was difficult for chili farmers to market their crops due to the closure of the venues and the enactment of the PSBB. This study aims to determine the impact of the Covid-19 pandemic on chili commodities. The research was conducted in Sei Mencirim Village, Deli Serdang Regency in May 2020. The research method used in this study was a survey method. The results showed that the average green chili farming income was Rp. 18,536,000 and Rp. 14,880,000 per one planting season. The profits obtained by farmers are certainly very small compared to the previous situation. This is due to the difficulty of marketing chilies during the Covid pandemic and the low prices of chilies. Farmers choose to harvest chilies when they are still green because they are more profitable in terms of production costs and storage capacity of chilies. Not only that, at harvest green chilies the size and weight of chilies are larger and require less maintenance such as fertilization, labor, spraying pests and other treatments.